Tactile maps as mediators in spatial interpretation - Tibola, Maiara (2023)
In this text, we bring aspects related to the importance of tactile maps, as teaching resources that mediate the geographic learning and knowledge of blind students. A case study in development, that takes place in the city of Francisco Beltrão-PR, with 15 teachers of Basic Education, that were interviewed about the teaching of included blind students and about the work with geographic concepts, both in regular education and in Specialized Educational Assistance, in the Multifunctional Resource Rooms - Visual Impairment Area (SRM-DV) and in the Pedagogical Support Center for Assistance to People with Visual Impairments (CAP). The methodology followed is the Critical Historical Theory, as a basis for the elaboration and adaptation of tactile didactic resources. The work is done at the Representations, Spaces, Times and Languages in Educational Experiences Research Group and Laboratory (RETLEE), of the Western Paraná State University (UNIOESTE), where the tactile map matrices are prepared based on the data collected through the research and in the indicative of the greatest need to study and teach about the relation of place in the world of the blind. The bases were built and evaluated by blind teachers and blind students. The maps were reproduced on acetate in the thermoforming machine. We continue saying that no pedagogical proposal alone can handle reality. So, we defend the Vygotsky's theoretical perspective, that indicates that the mediation of contents considers reality to provide knowledge and that the historical and social aspects of the studied context must be analyzed.